Changing epidemiology of hepatitis C virus genotypes in the central region of Argentina - Di Lello, Federico Alejandro (2015)
The aim of this study was to analyze the prevalence of hepatitis C virus (HCV) genotypes in Córdoba province, Argentina, over a 12-year period and to study the changes at the molecular level. The HCV genotype was determined in 357 HCV-infected patients, and the phylogeny and demographic reconstruction for HCV-1 was assessed. A significant reduction in HCV-2 prevalence with respect to HCV-1 in Córdoba after 2003 was observed. These findings are consistent with the epidemiological changes observed in South America. Nevertheless, the consequences of these changes remain to be elucidated.